FT-MS molecular composition data from two whitesand catchments in the lower Rio Negro basin from October/ November 2017 (end of dry season) - Carsten Simon; Tania P Pimentel; Maria Terezinha F Monteiro; Luiz A Candido; Didier Gastmans; Heike Geilmann; Regison da Costa Oliveira; João Batista Rocha; Elaine Pires; Carlos A Quesada; Bruce R Forsberg; Sávio J Filgueiras Ferreira; et al. (PANGAEA, 2020)
We investigated the role of whitesand ecosystems (WSEs) in blackwater formation in the Rio Negro basin in order to develop novel constraints for the terrestrial carbon export from land to ocean. Orbitrap mass spectrometry, a kind of ultrahigh resolution technique (FT-MS), allows to resolve thousand of individual molecular features per DOM sample. Precise determination of exact mass allows the assignment of molecular formulae to these features. We therefore identified molecular markers using Orbitrap mass spectrometry from dissolved organic carbon (DOC) of ground- and surface waters in two contrasting WSEs feeding Rio Negro tributaries and compared them with known Rio Negro markers. One tributary was fed by a whitesand riparian valley connected to a terra firme plateau, while the other was fed by a typical upland whitesand Campina. We sampled at the end of October and beginning of November 2017. "Data Set S1", an .xlsx file, contains the crosstab (samples in columns, formulae in rows) of all molecular formulae, the DOM index data (chemical indices calculated from the formula data), ecosystem averages (averages across DOM samples from the same ecosystem), ecosystem fingerprint assignments (indicative formulae per ecosystem type as assessed by t-tests, i.e., significantly "enriched" formulae based on ion abundance data), Rio Negro marker overlap (comparison of fingerprints with two sets of published Rio Negro markers from Gonsior et al. 2016 (doi:10.5194/bg-13-4279-2016) and Simon et al. 2019 (doi:10.1016/j.orggeochem.2019.01.013), and evaluation of structural data from PubChem (for those nine WSE formulae that showed consistent matching with Rio Negro markers). "Data Set S2", also an .xlsx file, contains the merged crosstab that was used for a general dataset comparison of whitesand DOM and the two openly available Rio Negro datasets. "Data Set S3" is a .docx file containing the list of structure suggestions for nine potential whitesand Rio Negro markers from PubChem, including the structural formulae (which are not provided in "Data Set S1").